Recent Advances on Metal-Based Near-Infrared and Infrared Emitting OLEDs - Malika Ibrahim-Ouali; Frédéric Dumur (Molecules, 2019)
During the past decades, the development of emissive materials for organic light-emitting diodes (OLEDs) in infrared region has focused the interest of numerous research groups as these devices can find interest in applications ranging from optical communication to defense. To date, metal complexes have been most widely studied to elaborate near-infrared (NIR) emitters due to their low energy emissive triplet states and their facile access. In this review, an overview of the different metal complexes used in OLEDs and enabling to get an infrared emission is provided.